1983
DOI: 10.1126/science.221.4615.1078
|View full text |Cite
|
Sign up to set email alerts
|

On Seeing Reddish Green and Yellowish Blue

Abstract: Four color names-red, yellow, green, and blue-can be used singly or combined in pairs to describe all other colors. Orange, for example, can be described as a reddish yellow, cyan as a bluish green, and purple as a reddish blue. Some dyadic color names (such as reddish green and bluish yellow) describe colors that are not normally realizable. By stabilizing the retinal image of the boundary between a pair of red and green stripes (or a pair of yellow and blue stripes) but not their outer edges, however, the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
0
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(61 citation statements)
references
References 11 publications
3
55
0
3
Order By: Relevance
“…The structure and specificity of RFs and of cortical functional architecture are increasingly seen as context dependent. This may represent the cellular mechanism of perceptual studies showing that the visual system is capable of linking contours and surfaces in a process of perceptual fill-in (2)(3)(4)(5)(6), that our perception of the attributes of local features is influenced by context (7)(8)(9)(10)(11)(12)(13)(14), and that simple contours can be picked out of a noisy background (15-18). The perceptual phenomena obey rules that are consonant with the patterns of connectivity in primary visual cortex, supporting the idea that a major component of the process of spatial integration occurs there.…”
mentioning
confidence: 99%
“…The structure and specificity of RFs and of cortical functional architecture are increasingly seen as context dependent. This may represent the cellular mechanism of perceptual studies showing that the visual system is capable of linking contours and surfaces in a process of perceptual fill-in (2)(3)(4)(5)(6), that our perception of the attributes of local features is influenced by context (7)(8)(9)(10)(11)(12)(13)(14), and that simple contours can be picked out of a noisy background (15-18). The perceptual phenomena obey rules that are consonant with the patterns of connectivity in primary visual cortex, supporting the idea that a major component of the process of spatial integration occurs there.…”
mentioning
confidence: 99%
“…(Crane/Piantanida1983, p. 1079. Also these subjects did not use the expression "reddish green", although they seem to have talked of perceiving one colour, which is not the same as saying that an "entire region can be perceived simultaneously as both red and green (or yellow and blue)" (Crane/Piantanida 1983, p. 1078. Since the experimenters think that these differences do not matter, I should rather be given a full record of what their subjects actually said.…”
Section: Wittgenstein On Conceptual Arbitrarinessmentioning
confidence: 99%
“…By stabilizing the retinal image of the boundary between a pair of red and green stripes (or a pair of yellow and blue stripes) but not their outer edges, however, the entire region can be perceived simultaneously as both red and green (or yellow and blue). (Crane/Piantanida 1983, p. 1078 I first want to note that it is not accurate to say that perceiving something to be of an "-ish" colour is the same as perceiving a surface as having two colours at the same time. When something is seen to be bluish green, for example, it is not blue and green at the same time.…”
Section: Wittgenstein On Conceptual Arbitrarinessmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps it is a lack of imagination on our part that it might seem that something couldn't look that way. And he cites research by Crane and Piantandia (1983) in which subjects reported that objects look both red and green at the same time.…”
Section: Apparent Color Incompatibilitymentioning
confidence: 99%